The 2dF galaxy redshift survey: Luminosity dependence of galaxy clustering - Norberg, P; Baugh, C; Hawkins, E; Maddox, S; Peacock, J; Cole, S; Frenk, C; Bland-Hawthorn, J; Bridges, T; Cannon, R; Colless, M; Collins, C; et al. (2001)
We investigate the dependence of the strength of galaxy clustering on intrinsic luminosity using the Anglo-Australian two degree field galaxy redshift survey (2dFGRS). The 2dFGRS is over an order of magnitude larger than previous redshift surveys used to address this issue. We measure the projected two-point correlation function of galaxies in a series of volume-limited samples. The projected correlation function is free from any distortion of the clustering pattern induced by peculiar motions and is well described by a power law in pair separation over the range 0.1 < (r/h-1 Mpc) < 10. The clustering of L*(Mbj - 5log10 h = -19.7) galaxies in real space is well-fitted by a correlation length r0 = 4.9 ± 0.3h-1 Mpc and power-law slope γ = 1.71 ± 0.06. The clustering amplitude increases slowly with absolute magnitude for galaxies fainter than M*. but rises more strongly at higher luminosities. At low luminosities, our results agree with measurements from the Southern Sky Redshift Survey 2 by Benoist et al. However, we find a weaker dependence of clustering strength on luminosity at the highest luminosities. The correlation function amplitude increases by a factor of 4.0 between Mbj - 5log10 h = -18 and -22.5, and the most luminous galaxies are 3.0 times more strongly clustered than L* galaxies. The power-law slope of the correlation function shows remarkably little variation for samples spanning a factor of 20 in luminosity. Our measurements are in very good agreement with the predictions of the hierarchical galaxy formation models of Benson et al.